Where we stand on doxyPEP depends on where we sit: a viewpoint - Vanbaelen, Thibaut; Kong, Fabian; Kanesaka, Izumo; Manoharan-Basil, Sheeba Santhini; Kenyon, Chris (Frontiers in Microbiology, 2025)
There is a striking variation in national doxycycline post exposure prophylaxis (doxyPEP) guidelines for sexually transmitted infections (STIs). Whilst some countries advocate doxyPEP for all men who have sex with men (MSM) and transgender women (TGW) with certain risks, others restrict the use to research settings. In this viewpoint, we argue that part of the explanation for this divergence can be attributed to different underlying conceptual frameworks. For individuals and organizations dominated by biomedical individualist frameworks, the primary goal of STI services is reducing the incidence of STIs. We have good evidence that doxyPEP does this and therefore, particularly in the setting of increasing STI incidence, this framework regards it as logical to roll out doxyPEP as fast as possible. By way of contrast, if organizations and their members operate within an ecosocial framework then their primary goal is the optimization of the sexual and overall health of individuals and populations and not just reducing STI rates. This framework sees the prevalence of STIs as being driven by the connectivity of local sexual networks. Recent increases in STI prevalence are seen as being due to increased network connectivity. The intensive use of antimicrobials such as doxycycline to reduce this prevalence is seen as introducing a selection pressure for the emergence of resistance to tetracyclines and other antimicrobials in N. gonorrhoeae and other species. This plus the other risks of doxyPEP, leads those animated by this framework to tend toward the precautionary principle and restrict the use of doxyPEP to research settings. The differences in these two frameworks thus leads different individuals and organizations with access to the same evidence-base to very different conclusions as to the net risk-benefit of doxyPEP.